2015
DOI: 10.1016/j.cardfail.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial of an Integrated Self-Care Intervention for Persons With Heart Failure and Diabetes: Quality of Life and Physical Functioning Outcomes

Abstract: Aims Persons with concomitant heart failure (HF) and diabetes mellitus (DM) have complicated, competing, self-care expectations and treatment regimens that may reduce quality of life (QOL). This randomized controlled trial tested an integrated self-care intervention on outcomes of HF and DM QOL, physical function and physical activity (PA). Methods Participants with HF and DM (n=134, mean age 57.4 ± 11 years, 66% men, 69% minority) were randomized to usual care attention control (control) or intervention gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 51 publications
2
62
0
4
Order By: Relevance
“…Physical function was measured using the six-minute walk test (6MWT) (Guyatt et al, 1985) a common field test shown to be reliable, valid, and safe in adults (including elderly adults) with a variety of medical conditions, including diabetes (Alfonso-Rosa, Del Pozo-Cruz, Del Pozo-Cruz, Sanudo, & Rogers, 2014; Dunbar et al, 2015; Ekman, Klintenberg, Bjorck, Norstrom, & Ridderstrale, 2013; Enright, 2003; Enright et al, 2003; Mangeri, Montesi, Forlani, Dalle Grave, & Marchesini, 2014; Pariser, Ann Demeuro, Gillette, & Stephen, 2010). The 6MWD has been shown to reflect the capacity for usual daily activities (Zeballos & Weisman, 2002) and walking ability (Ekman et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Physical function was measured using the six-minute walk test (6MWT) (Guyatt et al, 1985) a common field test shown to be reliable, valid, and safe in adults (including elderly adults) with a variety of medical conditions, including diabetes (Alfonso-Rosa, Del Pozo-Cruz, Del Pozo-Cruz, Sanudo, & Rogers, 2014; Dunbar et al, 2015; Ekman, Klintenberg, Bjorck, Norstrom, & Ridderstrale, 2013; Enright, 2003; Enright et al, 2003; Mangeri, Montesi, Forlani, Dalle Grave, & Marchesini, 2014; Pariser, Ann Demeuro, Gillette, & Stephen, 2010). The 6MWD has been shown to reflect the capacity for usual daily activities (Zeballos & Weisman, 2002) and walking ability (Ekman et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…20, 21 Participants were recruited during or within 3 months of an inpatient HF hospitalization at one of four participating urban hospitals between 2011 and 2013. All were large tertiary care facilities with HF outpatient clinics.…”
Section: Methodsmentioning
confidence: 99%
“…22 A detailed explanation of the intervention is available in the accompanying article that fully describes the primary goals and outcomes of the study. 20 The intervention was based on principles of adult learning, motivation and feedback, goal setting and provided both content and self-management strategies. 2328 The intervention was initiated in the hospital setting or soon after baseline data collection and study enrollment, and initially included an individualized educational and counseling session.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study supported by NINR demonstrated that an integrated intervention for individuals with both heart failure and diabetes was effective in improving components of self-care and had sustained effects on selected health care behaviors. (Dunbar et al, 2015)…”
Section: Nursing Research Relevant To Women’s Healthmentioning
confidence: 99%